IDENTIFIKASI DAMPAK PERUBAHAN IKLIM TERHADAP SERI DATA HUJAN DI PULAU JAWA - Wanny Kristyanti Adidarma (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2009)
The identification of climate change impacts on rainfall (annual, seasonal and monsoon rainfall) wasstudied using hundreds of rainfall data ranging from 1916-2006. The existence of trend in annual andseasonal rainfall series was detected by Statistical Test, namely Mann-Kendall and the Difference of TwoPopulations in monsoon series using Mann-Whitney.The results of the test showed that annual and seasonal rainfalls in most of the studied area had decreasedwhere others had increased. The monsoon rainfall showed a significant difference in frequency distributionparticularly in the months March-April-May (MAM) and December-January-February (DJF).